Policy Analysis and Implications for Sustainable Development Goals of Carbon Tax Implementation in Indonesia - Baba, Maria Anjelina; Candra, Yudas Tadius Andi (Research Horizon, 2025)
The continuous increase in carbon emissions in Indonesia over the past three decades has prompted the need for effective policy instruments to mitigate the impact of global warming. This study aims to analyze the implementation of the carbon tax in Indonesia and its relationship to the achievement of the Sustainable Development Goals (SDGs). The method used is descriptive qualitative with a public policy study approach through analysis of documents, regulations, and official national and international reports. The results show that the energy sector, especially coal-fired power plants, is the largest contributor to emissions, making it the initial target for the implementation of a carbon tax starting in 2022 at a rate of IDR 30/kg CO₂e through a cap and tax mechanism. This policy has the potential to reduce emissions while increasing fiscal revenue to support the energy transition, green development, and social protection. However, its effectiveness is still influenced by challenges such as limited sector coverage, industry readiness, and regulatory strengthening.